Pengaruh Pembiayaan Murabahah Terhadap Non Performing Financing Pada PT. Bank Brisyariah Tbk Periode 2012 – 2019 - akbar - azis; Mawaddah Warahmah; Haerana Haerana; Nurwahyuni Syahrir (Economy Deposit Journal (E-DJ), 2021)
The Effect of Murabahah Financing on Non-Performing Financing at PT. Bank BRISyariah, Tbk Period 2012 – 2019. This study aims to determine whether Murabahah financing has an effect on Non-Performing Financing as proxied by the ratio of non-performing financing or Non-Performing Financing (NPF). In order to achieve these objectives, this study uses a quantitative research type associative method. Regarding data collection, this study uses the documentation method by reviewing the financial statements of BRI Syariah Bank for 2012-2019 to obtain data related to Murabahah financing and Non-Performing Financing. The results showed that Murabahah financing had a positive and significant effect on Non-Performing Financing. From these results we can see that the higher the distribution of Murabahah financing carried out by BRI Syariah Bank, the NPF ratio can be reduced so that the bank's condition will remain in a healthy condition. Murabahah financing is only one of the many indicators of Non Performing Financing assessment, but still improving one indicator will certainly provide its own motivation to improve other indicators.